El Turismo Regenerativo como estrategia de educación y conservación ambiental en el corregimiento de Minca, Santa Marta, Colombia (2023)
The corregimiento of Minca in the Sierra Nevada de Santa Marta, Colombia, has experienced a growing tourist interest in recent years due to its natural beauty, its rich biodiversity and cultural history. Although tourism can be a source important source of income for the local community, it can also have a negative impact on the environment and local culture. (Institutional, 2023) The increase in tourism in Minca has had a significant impact on the environment. environment, manifesting itself in the loss of biodiversity, deforestation, water pollution and soil erosion, among other environmental problems (University of Magdalena, 2022). The Alma Mater study on the impacts of tourism on communities in Minca caused by tourism proposes to strengthen social capital and governance to build peace from community tourism. “This tourism has had some impacts pollutants in the river, grease from restaurants and hotels. has changed the agricultural vocation and these jobs are rarely occupied by natives of Minca, the benefits they have been precarious even in environmental terms.”